2022
DOI: 10.3892/ijo.2022.5325
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of birinapant in combination with carboplatin in targeting platinum‑resistant epithelial ovarian cancers

Abstract: Patients diagnosed with epithelial ovarian cancers (EOCs) often suffer from disease relapse associated with the emergence of resistance to standard platinum-based chemotherapy. Treatment of patients with chemo-resistant disease remains a clinical challenge. One mechanism of chemoresistance includes overexpression of pro-survival proteins called inhibitors of apoptosis (IAP) which enable cancer cells to evade apoptosis. Due to their anti-apoptotic activity, association with poor prognosis, and correlation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…Birinapant has extensive IAP antagonistic effects. Birinapant can cause rapid degradation of cIAP1, cleavage of PARP, activation of caspase, and inhibition of activation of NF-κB ( 45 ). The use of clofarabine and birinapant in gliomas has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Birinapant has extensive IAP antagonistic effects. Birinapant can cause rapid degradation of cIAP1, cleavage of PARP, activation of caspase, and inhibition of activation of NF-κB ( 45 ). The use of clofarabine and birinapant in gliomas has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“… 1 , 4 , 5 Confounding this is the fact that many OC cases will become platinum resistant and no longer respond to traditional therapies. 7 , 13 , 88 In this case, alternative approaches that are effective in treating OC patients is an unmet clinical need. 1 , 4 , 5 , 6 , 7 , 12 , 13 Here we have profiled a series of primary OC patient samples in the hopes to better understand the antigenic and environmental factors that distinguish chemonaive from recurrent, platinum-sensitive from platinum-resistant states, and how to more effectively target OC.…”
Section: Discussionmentioning
confidence: 99%
“…The combined treatment with birinapant (a SMAC mimetic compound) and carboplatin was found to be effective in various platinum-resistant EOC cell lines, in tumor samples and in PDX models. To simulate in-vivo responses, 3D organoid bioassay was successfully employed to study the combined effect of birinapant and carboplatin, which demonstrated improved anticancer efficacy that suggests the applicability of this model in pre-clinical studies (18).…”
Section: Use Of Smac Mimetics For Tumor Inhibitionmentioning
confidence: 99%